The Globus Galaxies platform: delivering science gateways as a service. (29th April 2015) - Madduri, Ravi; Chard, Kyle; Chard, Ryan; Lacinski, Lukasz; Rodriguez, Alex; Sulakhe, Dinanath; Kelly, David; Dave, Utpal; Foster, Ian
Summary: The use of public cloud computers to host sophisticated scientific data and software is transforming scientific practice by enabling broad access to capabilities previously available only to the few. The primary obstacle to more widespread use of public clouds to host scientific software ('cloud‐based science gateways') has thus far been the considerable gap between the specialized needs of science applications and the capabilities provided by cloud infrastructures. We describe here a domain‐independent, cloud‐based science gateway platform, the Globus Galaxies platform, which overcomes this gap by providing a set of hosted services that directly address the needs of science gateway developers. The design and implementation of this platform leverages our several years of experience with Globus Genomics, a cloud‐based science gateway that has served more than 200 genomics researchers across 30 institutions. Building on that foundation, we have implemented a platform that leverages the popular Galaxy system for application hosting and workflow execution; Globus services for data transfer, user and group management, and authentication; and a cost‐aware elastic provisioning model specialized for public cloud resources. We describe here the capabilities and architecture of this platform, present six scientific domains in which we have successfully applied it, report on user experiences, and analyze the economics of our deployments. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.